Contamination of Microplastic in Cockle at Paknam Prasae Sub-district, Klaeng District, Rayong Province, Thailand - Chowchaikong, Nittiya; Namjuntra, Pisit; Prommano, Oranan; Paojinda, Patsarawadee; Poorahong, Watcharaporn (Journal of Vocational Education in Agriculture, 2024)
Microplastics are now a common marine pollution problem that is affecting on the livelihood of organisms in marine ecosystems. The microplastic contamination in marine organisms are transferred to human via food chain. This study aims to investigate the contamination of microplastics in a total of 450 samples of cockles (Anadaragranosa Linnaeus) from Pak Nam Prasae, Klaengdistrict, Rayong province. Cockle samples were divided into 3 groups, including small cockles (<2.5 cm), medium cockles (2.5-3.0 cm) and large cockles (> 3.0 cm). The microplastics were analyzed using a phase contrast microscope at 40X magnification. The results showed that contamination of microplastic in the small cockles, medium cockles and large cockles with numbers of microplastic at 54.67±11.9, 13.49±3.5 and 19.56±3.8 particles/sample set, respectively. The most common forms and color of microplastics were irregular forms (51.10%) and red color (57.60%). This study revealed the microplastic contamination in cockles from the area of Pak Nam Prasae, Klaengdistrict, Rayong province. These results can be used as a basic information to raise awareness of the pollution of microplastics entering the marine organism and the marine environment, leading to human health risk.